Fluorescent probes for the detection of disease-associated biomarkers - Dou, Wei-Tao; Han, Hai-Hao; Sedgwick, Adam C.; Zhu, Guo-Biao; Zang, Yi; Yang, Xin-Rong; Yoon, Juyoung; James, Tony D.; Li, Jia; He, Xiao-Peng (Science bulletin, 2022)
[Display omitted] Fluorescent probes have emerged as indispensable chemical tools to the field of chemical biology and medicine. The ability to detect intracellular species and monitor physiological processes has not only advanced our knowledge in biology but has provided new approaches towards disease diagnosis. In this review, we detail the design criteria and strategies for some recently reported fluorescent probes that can detect a wide range of biologically important species in cells and in vivo. In doing so, we highlight the importance of each biological species and their role in biological systems and for disease progression. We then discuss the current problems and challenges of existing technologies and provide our perspective on the future directions of the research area. Overall, we hope this review will provide inspiration for researchers and prove as useful guide for the development of the next generation of fluorescent probes.